BETWEEN INCLUSION & EXCLUSION: THE DIGITAL LIVES OF UNDOCUMENTED IMMIGRANTS IN THE UNITED STATES - Bastick, Zach; Mallet, Marie L. (AoIR Selected Papers of Internet Research, 2021)
Undocumented immigrants are a highly vulnerable group that can both benefit and suffer from digital technologies. However, little is known about their digital inclusion and the ways in which this amplifies or attenuates the vulnerabilities of their undocumented status. This paper provides rare and novel evidence from 44 in-depth interviews with undocumented Latino immigrants in the United States. It reports on findings regarding the digital employment of undocumented immigrants, the use of the internet in supporting their transnational family practices, and their uses and attitudes towards telehealth services. It highlights the importance of providing insight and analysis on digital life at the margins of society.